Cost-oriented analysis of fibre reinforced concrete column-supported flat slabs construction. (1st July 2022) - Aidarov, Stanislav; Nadaždi, Ana; Pugach, Evgeniy; Tošić, Nikola; de la Fuente, Albert
Abstract: Fibre reinforced concrete (FRC) is increasingly being used in elements with high structural responsibility, the constructed FRC column-supported flat slabs (CSFSs, hereinafter) with partial or even total substitution of reinforcing steel bars being a supporting evidence for that statement. These pioneer experiences provide encouraging results with respect to resource optimization and construction time reduction without jeopardising the structural reliability. Despite such promising achievements, the use of FRC in CSFSs is still limited in the building sector. To provide an additional impulse for the use of FRC, a comprehensive comparison between FRC and traditional reinforced concrete (RC) technologies for CSFSs in terms of execution procedure and overall costs is needed. With this in mind, an industrial-oriented study was carried out with the main objective of elaborating a simplified method for the preliminary comparison of RC and FRC solutions. This method permits to assess the major amount of the required reinforcement (flexural reinforcement) followed by an evaluation of the time saving effect due to the partial or total substitution of reinforcing steel bars by fibres. For this purpose and for the sake of generalization, several databases were examined and 33 interviews with experts on in situ construction were conducted so that a wide range of productivity rates and other particularities could be identified. Based on the proposed method, a case study was analysed in order to indicate the potential direct costs (materials + labour) for a number of RC and FRC solutions using data from the examined databases and conducted interviews. The results reflect an increment of direct costs for both fibre and hybrid (fibre + reinforcing steel bars, HFRC) solutions; however, these increment can be compensated by the reduction of the construction period and, as a consequence, time-dependent costs (i.e., preliminaries, equipment costs, overheads, and finance costs). The outcomes of this research are meant to provide support to designers and construction planners with regard to the suitability of using FRC for CSFSs. Highlights: A method to quantify the flexural reinforcement for FRC flat slabs is proposed. Basis for quantifying the material and labour costs for RC/FRC flat slabs is provided. 33 construction experts were interviewed to identify magnitudes of productivity rates. A time saving effect is observed due to use of FRC-based solutions.